Tantangan Tantangan dan Inovasi dalam Program Kampus Mengajar KemendikbudRistek 2023 : Studi Kasus di SD Negeri 1 Bira - Hermanto Z. Mautang; Deven T. Malihing; Oualeng, Adolfina; Adryel O. Palle; Aisyah Mau (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
The role of education in building the country and the vision of national education based on law No. 20 of 2003. In the era of the industrial revolution 4.0, educational challenges are increasingly complex due to technological advances. The Indonesian Ministry of Education and Culture and Research and Technology responded by launching the Teaching Campus Program to improve the quality of education in elementary schools. This program involves collaboration between higher education and elementary schools and provides opportunities for students to interact directly with the world of education. Selected students are placed in leading, disadvantaged and outermost (3T) schools to improve the quality of education in the area. The program also has a positive impact on students by developing creativity, interpersonal skills, and leadership. This study analyzed the implementation of the campus teaching program at SD Negeri 1 Bira, Alor Regency. With the aim of understanding the transformation of education in the era of the industrial revolution 4.0. This research also involved students, field assistant lecturers, and the school in developing the program. In conclusion, this program has a positive impact on the quality of learning in elementary schools and encourages technology adaptation in education.